Hybridization of plasmons in coupled nanowires - Sakhnenko, N. K.; Stognii, N. P. (IEEE, 2012)
Theoretical study of plasmon resonant eigenfrequencies in metal nanowires is presented. Mechanism of the plasmonic mode coupling that can be considered as symmetric and antisymmetric combinations of isolated wires plasmons is investigated. Accurate analysis of the spectrum of different plasmon resonances is presented.
Keywords: surface plasmons; plasmon eigenfrequency